Numerical simulation of well location deployment scheme for CO2 sequestration in old goaf - Yang DING; Yuanzhuo TANG; Shugang LI; Hongchao ZHAO; Bing ZHU; Yizheng ZHANG; Yan ZHANG (Meitan kexue jishu)
As a potential CO2 storage geologic body, the old goaf has great storage potential. In order to clarify the distribution characteristics and storage capacity of CO2 injection in the old goaf under different monitoring well deployment schemes, based on the actual geological conditions of the experimental coal mine in Huangling Mining area, the numerical simulation of CO2 injection in the old goaf was carried out by using COMSOL software on the basis of considering the permeability heterogeneity and the differences in the adsorption capacity of coal and rock in the old goaf. The results show that the distribution of CO2 in the old goaf is closer to the floor, the distribution range is wider and the concentration is higher. When the depth of the injection well reaches 65m, the CO2 distribution in the low permeability area in the upper part of the old goaf increases significantly, while the trend distribution decreases significantly, and the total and free CO2 storage reach the maximum value, which are 7.594×106 kg and 3.569×106 kg, respectively. When the depth of injection well is 95 m, the storage of adsorbed CO2 is the largest, and the proportion of total storage is the highest, which are 4.37×106 kg and 63.52%, respectively. With the increase of the number of monitoring Wells, the distribution range of CO2 in the strike of the old goaf is significantly expanded. In addition, by in creasing the number of monitoring Wells and adopting symmetrical deployment, the range of coal and rock mass in the old goaf participating in adsorption storage is expanded, thus increasing the proportion of CO2 sealed in the old goaf and adsorbed storage. Under this arrangement, the CO2 sealed stock is more than 1.82 times that of the single monitoring well. The proportion of CO2 storage in adsorbed state increased from 53.22% to 72.693%. Based on the analysis of the distribution characteristics and sealing stock, the longitudinal injection points and monitoring well deployment methods which are conducive to improving the CO2 sealing stock in the old goaf are obtained, which can provide an important reference for the CO2 sealing well deployment scheme in the old goaf.